Intra-articular hyaluronic acid injections and oral collagen supplementation for knee OA: A case report of an elite female soccer player - Tarantino, D.; Sirico, F.; Corrado, B.; Ruosi, C. (Journal of Human Sport & Exercise, 2021)
Soccer players are susceptible to repeated trauma that could lead to a precocious development of knee osteoarthritis (OA). Intra-articular hyaluronic acid (IA-HA) injections have been proposed as a valid treatment for knee OA. Objectives: To describe the effects of IA-HA injections and oral collagen supplementation in a female soccer goalkeeper playing in Italian Women`s Serie A with secondary OA in her knee. Design: Case report. Setting: The athlete underwent three IA-HA injections (1 per week for 3 weeks in a row) together with oral collagen supplementation for one month. Treatment outcomes were evaluated using five scoring scales. Results: One week after the first IA-HA injection all the scores improved. One week after the second injection, compared with the first week, two scores improved, two remained the same, and one worsened. One week after the third injection, compared with the second week, all the scores worsened. At one month, compared with the third week, one score remained the same and all the others worsened. From baseline to one month, three scores improved, one remained the same, and one worsened. Conclusions: In our study, IA-HA injections and oral collagen supplementation showed short-term effects on pain and functional impairment for knee OA.